If you can factorize (or "unFoil" the expression, you will find the zeroes.
Else, you could use the quadratic formula, or by completing squares.
math - 3xsquared + 27 = 5 3xsquared -5x = -3xsquared + 6 SOLVE
math check my answers - 1. 2(x+3)squared-6x+5=0 Answer= 2xsquared+6x+23=0 2. ...
geometry - how do you unfoil 3xsquared+5x-2=0?
Intermediate Algebra - Please help with the below. I know the answer I need help...
algebra - y=3(x+5)(x-2) I'm suppose to simplify right? There is no way to solve ...
college algebra - h(x)=3xsquared+5x-3
college agebra - (3xsquared-2x-1)(xsquared+x+5)
Pre algebra - X cubed-3xsquared-2x+15
math - (3xsquared-7x-6)+(2xsquared-4x+1) simplify
9th grade - Need help with (x+5)(3xsquared-2x+1)